Tension between local, regional and national level in Norwegian handling of COVID-19 - Anette Fosse; Birgit Abelsen; Anders Svensson; Ingvill Konradsen (James Cook University, 2023)
Introduction: The initial phase of the COVID-19 pandemic can be described as a crisis - a threat that must be urgently addressed under conditions of deep uncertainty. We wanted to explore the tension between local, regional and national authorities evoked by some rural municipalities’ decisions to impose local infection control measures during the first weeks of the COVID-19 pandemic in Norway.Methods: Eight municipal chief medical officers of health (CMO) and six crisis management teams participated in semi-structured and focus group interviews. Data were analyzed with systematic text condensation. Boin and Bynander’s interpretation of crisis management and coordination and Nesheim et al.’s framework for non-hierarchical coordination in the state sector inspired the analysis.Results: Uncertainty in the face of a pandemic with unknown damage potential, lack of infection control equipment, patient transport challenges, vulnerable staff situation and planning of local COVID-19 beds were some of the reasons for rural municipalities imposing local infection control measures. Local CMOs’ engagement, visibility and knowledge contributed to trust and safety. Differences in perspectives between local, regional and national actors created tension. Existing roles and structures were adjusted, and new informal networks arose.Discussion: Strong municipal responsibility in Norway and the quite unique arrangement with local CMOs in every municipality with legal right to decide temporary local infection control measures seemed to facilitate a fruitful balance between top-down and bottom-up decision-making. The following dialogue and mutual adjustment of perspectives led to appropriate balance between national and local measures in Norway’s handling of the COVID-19 pandemic.